STUDENTS’ DIFFICULTIES IN WRITING ADJECTIVE PHRASES - Yasti Kurniasari; Tina Priyantin; Yanti Suryanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2019)
ABSTRACTStudents of EFL countries find it difficult to break down their ideas from their native language into English, and one of the difficulties is related to conduct adjective phrases. The objective of this research is to discover kinds of difficulties that students face in writing adjective phrases. Qualitative research is applied in order to explain the problem more specifically and descriptive method is employed to maintain alongside the approach used. Triangulation data turn to be the instruments which include documentation, questionnaire distribution and semi-structured interview. The class for participating in this research is 4th semester of English students in Pakuan University. Students are participating in documentation by compiling their essays to identify glitches in adjective phrases before questionnaire session. Meanwhile, interview session is conducted to the lecturer of the essay writing class. The result shows that error in addition (56.67%) becomes the highest rate, then selection (21.67%), omission (15%) and ordering (6.67%). Associated with the reasons above, there are two major causes of students’ difficulties, namely interlingual and intralingual errors, but then the data show that students struggle in Mother Tongue Interference.Keywords: Writing Ability, Grammar, Interlingual Errors, Mother Tongue Interference (MTI) ABSTRAKMahasiswa dari negara yang menggunakan Bahasa Inggris sebagai bahasa asing menghadapi kesulitan untuk mengekspresikan ide dari bahasa penutur asli ke bahasa Inggris, salah satu kesulitannya mengacu pada merangkai frasa kata sifat. Tujuan dari penelitian ini adalah untuk mendapatkan klasifikasi kesulitan saat mahasiswa menyusun frasa kata sifat. Penelitian kualitaitf diterapkan untuk menjelaskan kendala lebih spesifik, serta dilengkapi dengan metode penelitian deskriptif.agar mempertegas pendekatan penelitian yang digunakan. Instrumen yang digunakan yaitu Triangulasi yang mencangkup dokumentasi, angket dan wawancara. Kelas yang berpartisipasi dalam penelitian merupakan mahasiswa semester empat prodi Bahasa Inggris di Universitas Pakuan. Mahasiswa andil dalam dokumentasi yang berupa pengumpulan esai untuk mendeteksi kesalahan dalam frasa kata sifat sebelum mengacu ke angket. Sedangkan wawancara ditujukan kepada dosen pengampu mata kuliah bersangkutan. Hasil penelitian mengindikasikan kesalahan di penambahan kata (56.67%) menempati urutan pertama, disusul dengan pemilihan kata (21.67%), pengurangan kata (15%) serta runtutan kata (6.67%). Berdasarkan perolehan diatas, terdapat dua penyebab utama kesulitan mahasiswa, yakni kesalahan interlingual dan intralingual, namun hasil penelitian menyatakan bahwa mahasiswa menghadapi kesulitan dalam pengaruh bahasa ibu.Kata kunci: Kemampuan Menulis, Tatabahasa, Kesalahan Interlingual, Bahasa Ibu